Efficacy of galium-68 dotatate pet/ct in the detection of metastasis rate of well-differentiated gastroenteropancreatic neuroendocrine tumors - Komek, Halil; Balci, Tansel Ansal; Can, Canan (Mashhad University of Medical Sciences, 2019)
Objective(s): The aim of this study was to determine metastasis rate in patients with well-differentiated grade1 (G1) and grade 2 (G2) gastroenteropancreatic neuroendocrine tumors (GEP NETs) using the gallium-68 DOTATATE positron emission tomography/computed tomography (68Ga-DOTATATE PET/CT). This study was also targeted toward investigating the relationship of maximum standardized uptake value (SUVmax) with mitotic count, histological grade, and Ki-67 index. Methods: This retrospective study included 38 patients (i.e., 17 males and 21 females) with G1 or G2 GEP NETs who underwent68Ga-DOTATATE PET/CT in Diyarbakir Gazi Yasargil training and research hospital between November 2014 and March 2018. The patients had at least one positive lesion that was approved by two nuclear medicine specialists with a minimum of 10 years of experience. Results: The median age of the patients was 50 years (age range: 27-80 years), and their mean age was 52±15 years. Out of 38 patients, 1 (2.6%), 2 (5.2%), 2 (5.2%), 3 (7.8%), 10 (28.5%), and 19 (50%) patients had primary hepatic, primary mesenteric, colon, duodenal, gastric, and pancreatic NETs, respectively. In addition, the liver metastasis, local lymph node invasions, distant lymph node metastasis, bone metastasis, peritoneal involvement, and lung metastasis were observed in 42%, 21%, 15.7%, 13%, 7.8%, and 5% of the cases, respectively. The SUVmax median values of G1 and G2 tumors were 9.45 (range: 4.2-43.6) and 34.9 (range: 4.1-103), respectively (P=0.003). The Ki-67 index showed a negative correlation with the SUVmax value of the liver metastases and the highest SUVmax value (P=0.001 and P=0.002, respectively). There was also a negative correlation between mitosis count and the highest SUVmax value (P=0.011). Conclusion: Based on the findings, although [68Ga]DOTATATE PET/CT is successfully used to diagnose primary GEP NETs and their metastases, the SUVmax value obtained from DOTATATE PET/CT showed a negative correlation with Ki-67 and mitotic count. © 2019 mums.ac.ir All rights reserved.
Keywords: 68Ga-DOTATATE; Gastroenteropancreatic (GEP); Neuroendocrine tumor (NET); PET/CT